POTENSI LIMBAH KULIT PISANG KEPOK (Musa paradisiaca) SEBAGAI BAHAN BAKU PEMBUATAN ASAM ASETAT MENGGUNAKAN BERBAGAI MACAM STARTER - Ilham '; Itnawita '; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Kepok banana (Musa paradisiaca) peel waste contain sugar that can be changed to acetic acid using Effective Microorganism (EM-4), kombucha (KO), cassava yeast (RT) and instant yeast (RI) (commercial starter). The Commercial starter contains variety of bacteria and yeasts with different content of microorganism that will influence the amount of ethanol produced. The aim of this study to determine the potential of kepok banana peel waste used as the main material in synthesis of acetic acid using commercial starter. Based on the fermentation results using the four starter, cassava yeast has a good ability to be fermented. The acetic acid formation was obtained under condition which substrate and starter amount are 80% w/v and 5 grams respectively and fermentation time 4 day. Based on these conditions it was found that the amount of organic acid total determined by titrimetric method is 4.712±0.066% and acetic acid formed which was determined by Ion Chromatography method is 0.7507± 0.0538%.